EVALUASI PELAKSANAAN PROGRAM TERAPI RUMATAN METADON PADA PECANDU NARKOBA JENIS PUTAW DI KOTA SEMARANG TAHUN 2016 (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2017)
Methadone maintenance treatment (MMT) is aimed to reduce the harmful effects of injecting drug use. Since the first Puskesmas Poncol opened this program in 2010, there were 50 users of MMT. Currently users of MMT were 11 people, 2 people have died, no patient has recovered, and 36 others dropped out. Those did not recover, but dropped out with reasons and information that were not known by the officer. MMT is a strategic key of HIV/ AIDS prevention for injecting drug users. However, in the implementation Puskesmas Poncol was lost most of active MMT users. The research aimed to know the implementation of MMT which includes input, process, and output on heroin addict in Puskesmas Poncol. This research was qualitative research supported by quantitative data. Data collection used in-depth interviews, observation, and documentation. The result of the research showed that the service of MMT in Puskesmas Poncol was still many weaknesses, from input aspect (untrained human resources), process (methadone planning, organizing, and dose arrangement have not been well implemented), and output (services have not been evaluated).